The Role of Team Activities and External Support Environment in Leadership Development: An Emotional Intelligence Perspective - Li, Yukun; Tuntinakhongul, Ampapan (Journal of Posthumanism, 2025)
Understanding the factors that shape leadership development is crucial for preparing individuals to effectively lead in diverse and dynamic environments, making this study particularly significant as it explores the roles of team activities, family support, and campus environments in fostering leadership, with emotional intelligence as a key mediating factor. This study investigates the key factors influencing university student leadership development, focusing on the role of team activities, family environment, and campus environment, with emotional intelligence acting as a mediating variable. A stratified random sampling method was used to gather data universities in Guangdong Province, China. Structural equation modeling (SEM) was applied to assess the relationships between these variables. The results revealed that team activities, family environment, and campus environment significantly impact leadership development, both directly and indirectly through emotional intelligence. These findings offer valuable insights into improving leadership training programs in higher education, emphasizing the importance of enhancing emotional intelligence and providing supportive environments.